Pesan Komunikasi Dakwah Rasulullah - Muhammad Al Fatih (Program Studi Komunikasi dan Penyiaran Islam IAI Pangeran Diponegoro Nganjuk, 2025)
The purpose of this study is to describe the content of the Prophet's da'wah communication message through the letters of the Prophet to the kings. The kings in question are Najasyi king of Habashah, Muqauqis king of Egypt, Kisra king of Persia, Heraklius emperor of Rome, Al-Mundzir bin Sawa ruler of Bahrain, Haudzah bin Ali ruler of Yamamah, Al-Harith bin Abu Shamr Al-Ghassani Ruler of Damascus, Jaifar and Abd. bin Al-Julunda king of Oman. The research method used is the message analysis method. The results of the study can be concluded that the content of the message of the Prophet Muhammad Saw. through letters to the kings has the following message content; (1) Always begins with the Basmalah sentence, (2) Including the identity of the sender of the letter, namely Muhammad Rasulullah or Muhammad bin Abdullah, (3) Writing the name of the recipient of the letter, (4) The letter contains the content of the message of Theology or Tawhid, (5) There is a polite message of invitation to Islam and accompanied by Koranic arguments, (6) Providing motivational sentences or motives for gifts if you follow Islam, (7) Including a warning sentence as a consequence if you do not follow Islam.